2006
DOI: 10.1111/j.1420-9101.2005.00970.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid temporal change in the expression and age-related information content of a sexually selected trait

Abstract: The expression of sexual signals is often phenotypically plastic and also evolves rapidly. Few studies have considered the possibility that proximate determination – the pathway between genes and trait expression – may also be subject to both phenotypic plasticity and evolutionary change. We examined long‐term patterns in size, condition‐ and age‐dependence, repeatability and heritability of forehead patch size, a sexually selected plumage trait in male collared flycatchers. We also estimated survival and sexu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
1
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 90 publications
5
41
1
1
Order By: Relevance
“…It is sexually selected, but it seems that its information content differs between populations. Our results show that male forehead patch size did not predict lifetime offspring recruitment, and this result is consistent with those of earlier studies performed in this population, suggesting that the forehead patch is a poor indicator of phenotypic quality in our birds (Hegyi et al 2002(Hegyi et al , 2006a, but see Hegyi et al 2010), in contrast to the Swedish population (Gustafsson et al 1995; also see Gustafsson and Qvarnström 2006). It is possible that the advantage of a large forehead patch can only be detected in extra-pair paternity, for example if large-patched males sire more extra-pair young that return to breed.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…It is sexually selected, but it seems that its information content differs between populations. Our results show that male forehead patch size did not predict lifetime offspring recruitment, and this result is consistent with those of earlier studies performed in this population, suggesting that the forehead patch is a poor indicator of phenotypic quality in our birds (Hegyi et al 2002(Hegyi et al , 2006a, but see Hegyi et al 2010), in contrast to the Swedish population (Gustafsson et al 1995; also see Gustafsson and Qvarnström 2006). It is possible that the advantage of a large forehead patch can only be detected in extra-pair paternity, for example if large-patched males sire more extra-pair young that return to breed.…”
Section: Discussionsupporting
confidence: 82%
“…Whereas studies in a population in Gotland, Sweden, showed that the size of this trait was a good indicator of phenotypic quality (Gustafsson et al 1995;Qvarnström 1999; also see Gustafsson and Qvarnström 2006), this is not the case in our population (Hegyi et al 2002(Hegyi et al , 2006a, although the trait is an important determinant of social mating success (Hegyi et al 2010). The male forehead patch size was estimated as the product of its maximum height and maximum width.…”
Section: Study Species and Field Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our Hungarian study population, however, wing patch size is unrelated to extra-pair paternity (Rosivall et al 2009), but it is a condition-dependent signal (Török et al 2003) and has an important role in male territorial behaviour (Garamszegi et al 2006). On the other hand, forehead patch is a condition-dependent signal in the Swedish population (Gustafsson et al 1995;Sheldon et al 1997;Qvarnström 1999) but not so in our Hungarian population (Hegyi et al 2002(Hegyi et al , 2006b. Still, there is some indication in our population as well that males with large forehead patch are of better quality; that is the song rate of large-patched males decreases less after immune challenge (Garamszegi et al 2004) and large-patched males start to breed earlier in the season (Hegyi et al 2006b).…”
Section: Introductionmentioning
confidence: 77%
“…On the other hand, forehead patch is a condition-dependent signal in the Swedish population (Gustafsson et al 1995;Sheldon et al 1997;Qvarnström 1999) but not so in our Hungarian population (Hegyi et al 2002(Hegyi et al , 2006b. Still, there is some indication in our population as well that males with large forehead patch are of better quality; that is the song rate of large-patched males decreases less after immune challenge (Garamszegi et al 2004) and large-patched males start to breed earlier in the season (Hegyi et al 2006b). In the Swedish Collared Flycatcher population, the forehead patch plays an important role in mate choice (Sheldon et al 1997), but in our Hungarian population the results are mixed (Michl et al 2002;Garamszegi et al 2004;Rosivall et al 2009).…”
Section: Introductionmentioning
confidence: 77%